MODERN REQUIREMENTS FOR ACCOUNTING MANAGEMENT FOR PROVISION PROCESS - Zarudna, Nataliia (Journal of European Economy, 2017)
The following article deals with the issue of accounting management for provision process and its main requirements, in compliance with high technologies. The background, stages and tasks are determined, to be met within the process of accounting management. The model of organization of the provision process accounting is constructed based on the system-wise approach.